2000
DOI: 10.1128/jb.182.5.1313-1320.2000
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of the Linear Chromosome during Sporulation of Streptomyces coelicolor A3(2) Involves an oriC -Linked parAB Locus

Abstract: Candidate partitioning genes (parA and parB) for the linear chromosome of Streptomyces coelicolor were identified by DNA sequencing in a series of seven genes located between rnpA and trxA near the chromosomal replication origin. The most likely translation start point of parB overlapped the parA stop codon, suggestive of coregulation, and transcription analysis suggested that the two genes formed an operon. Deletion of part of parB had no effect on the growth or appearance of colonies but caused a deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(141 citation statements)
references
References 43 publications
5
136
0
Order By: Relevance
“…At present, their exact function is still unclear. It was, however, demonstrated that ParB interacts with conserved binding sites which are clustered in the origin-proximal region Easter and Gober, 2002;Bartosik et al, 2004] and that both proteins are necessary for proper chromosome segregation [Glaser et al, 1997;Mohl and Gober, 1997;Marston and Errington, 1999;Kim et al, 2000;Lewis et al, 2002]. With the exception of C. crescentus, however, deletion of parA or parB is not lethal and only results in mild growth phenotypes, which might imply redundancy in the systems that control positioning of the chromosome.…”
Section: Chromosome Segregationmentioning
confidence: 99%
“…At present, their exact function is still unclear. It was, however, demonstrated that ParB interacts with conserved binding sites which are clustered in the origin-proximal region Easter and Gober, 2002;Bartosik et al, 2004] and that both proteins are necessary for proper chromosome segregation [Glaser et al, 1997;Mohl and Gober, 1997;Marston and Errington, 1999;Kim et al, 2000;Lewis et al, 2002]. With the exception of C. crescentus, however, deletion of parA or parB is not lethal and only results in mild growth phenotypes, which might imply redundancy in the systems that control positioning of the chromosome.…”
Section: Chromosome Segregationmentioning
confidence: 99%
“…During vegetative growth, deletion of the parAB genes of Pseudomonas putida slightly increases the formation of anucleate cells, but during both the transition from exponential to stationary growth conditions and during overexpression of parAB, high levels of anucleate cells were formed (Godfrin-Estevenon et al 2002). Deletion of parAB in Streptomyces coelicolor had no detectable effect in vegetatively growing cells, but also resulted in the production of significant numbers of anucleate spores (Kim et al 2000).…”
Section: Par Proteins Encoded By Bacterial Chromosomes-components Of mentioning
confidence: 99%
“…ParA is an ATPase that binds ParB and is proposed to direct the ParB/parS complex to the poles (18). These partitioning systems serve to facilitate chromosome segregation but are often not essential, for example, in B. subtilis, Streptomyces coelicolor, and Pseudomonas putida and for V. cholerae chromosome I (18,23,30,35).In contrast, these systems are essential for viability in C. crescentus (41,54) and for segregation of chromosome II in V. cholerae (63). The latter requirement may be due to the fact that chromosome II has many properties of a large plasmid and its Par proteins are more closely related to plasmid-encoded ones than to those encoded on chromosomes (22).…”
mentioning
confidence: 99%
“…ParA is an ATPase that binds ParB and is proposed to direct the ParB/parS complex to the poles (18). These partitioning systems serve to facilitate chromosome segregation but are often not essential, for example, in B. subtilis, Streptomyces coelicolor, and Pseudomonas putida and for V. cholerae chromosome I (18,23,30,35).…”
mentioning
confidence: 99%